Genetical and Biochemical Study in Duchenne muscular dystropy ca rriers - Ibrahim, H. I.; Hasson, A.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Six females definite Duchennc carriers and 8 females of possible carriers were examine in this study by serum C.P.K after exercise and muscle Biopsy for histochemical study. This st udy was compared with that of normal person. The scnm1 C.P.K was found to be highly elevated in all the 14 catTiers, while slight - moderate elevation was found in normal control. All the definite carriers and 6 ex pected gave abnormal histochemistry in their muscles. the other 2 gave no definite abnormality. So these tests can be used in the (uturc for assessment of Duchenne carriers.